Pengaruh Kepercayaan dan Kualitas Pelayanan terhadap Keputusan Nasabah dalam Menggunakan Produk Pembiayaan di Koperasi BMT Al-Ishlah Kota Jambi - Ana Sukma Aprilla; Ahmad Syahrizal; Saijun Saijun (Universitas Kristen Indonesia Toraja, 2026)
Trust and service quality are important factors that can influence customer decisions in using financing products at Islamic financial institutions. The BMT Al-Ishlah Cooperative in Jambi City, as one of the Islamic microfinance institutions, is required to be able to increase trust and provide quality services to attract customer interest. This study aims to determine the effect of trust and service quality on customer decisions in using financing products using a quantitative associative approach method and a sample of 76 respondents. The instruments used were observation and a questionnaire with a Likert scale. Data analysis techniques used in this study include descriptive analysis, validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, partial tests (t-tests), simultaneous tests (F-tests), and coefficients of determination (R²). The results show that partially trust has a positive but insignificant effect on customer decisions, while service quality has a positive and significant effect. Simultaneously, trust and service quality have a significant influence on customer decisions with a coefficient of determination (R²) value of 0.662 or 66.2%, which means that the variables of trust and service quality are able to explain customer decisions by 66.2%, while the remaining 33.8% is influenced by other variables outside this study.